2023
DOI: 10.3389/fimmu.2022.1010700
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of conditioned media of immortalized stem cells from human exfoliated deciduous teeth on pressure ulcer formation

Abstract: Pressure ulcers (PUs) are increasing with aging worldwide, but there is no effective causal therapy. Although mesenchymal stem cells (MSCs) promote cutaneous wound healing, the effects of the conditioned medium (CM) of MSCs on cutaneous PU formation induced by ischemia-reperfusion injury have been poorly investigated. To address this issue, herein, we first established an immortalized stem cell line from human exfoliated deciduous teeth (SHED). This cell line was revealed to have superior characteristics in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…The in vivo study by Hiraki et al (2020) also proposed cytokines and growth factors in SHED-derived secretome, particularly M-CSF, ANG, VEGF-A, MCP-1, VEGF-C, and bFGF, to be the main actors in the angiogenesis in the calvarial bone defect model of a mouse [64]. Additionally, VEGF, together with HGF, were also found to play roles in angiogenesis stimulation in the pressure ulcer mouse model [76].…”
Section: Effect Of Shed-derived Secretome On Angiogenesismentioning
confidence: 99%
“…The in vivo study by Hiraki et al (2020) also proposed cytokines and growth factors in SHED-derived secretome, particularly M-CSF, ANG, VEGF-A, MCP-1, VEGF-C, and bFGF, to be the main actors in the angiogenesis in the calvarial bone defect model of a mouse [64]. Additionally, VEGF, together with HGF, were also found to play roles in angiogenesis stimulation in the pressure ulcer mouse model [76].…”
Section: Effect Of Shed-derived Secretome On Angiogenesismentioning
confidence: 99%
“…Indeed, numerous studies have shown that autologous transplantation of SHEDs, for example, may be a safe and promising approach for both dentin and pulp regeneration (reviewed in [ 28 ]), but their applications far exceed the orthodontic field, as SHEDs have also been tested for their regenerative potential against spinal cord injury [ 29 , 30 , 31 ], hypoxic–ischemic brain injury [ 32 ], ovariectomy-induced osteoporosis [ 33 ], liver fibrosis [ 34 ], and systemic lupus erythematosus [ 35 ]. And that potential lies not only in the cells themselves but also in the conditioned media one may collect from their culture, as elegantly shown by Katahira and co-workers in a recent study, where they immortalized a SHED cell line and analyzed the effects of its conditioned medium on cutaneous pressure ulcers [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…But their applications far exceed the orthodontic field, as SHEDs have also been tested for their regenerative potential against spinal cord injury [ [29][30][31], hypoxic-ischemic brain injury [32], ovariectomy-induced osteoporosis [33], liver fibrosis [34], and systemic lupus erythematosus [35]. And that potential lies not only on the cells themselves but also in the conditioned media one may collect from their culture, as elegantly shown by Murakami and co-workers in a recent study, where the authors immortalized a SHED cell line, and analysed the effects of its conditioned medium on cutaneous pressure ulcers [36].…”
Section: Introductionmentioning
confidence: 99%